BEYOND BUSINESS CREATION: PERAN PENDIDIKAN KEWIRAUSAHAAN SEBAGAI INKUBATOR BERPIKIR KRITIS DALAM TINJAUAN LITERATUR SISTEMATIS - Haniatur Rofiqoh Umar; Shahrul Dwi Ananta; Wening Patmi Rahayu; Andy Prasetyo Wati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Entrepreneurship education plays a crucial role in enhancing the critical thinking skills of vocational high school (SMK) students. This study employed a Systematic Literature Review (SLR) method by analyzing 9 selected articles from a total of 16,100 publications between 2020 and 2025. The study aims to demonstrate that the implementation of learning methods and entrepreneurship programs in SMKs effectively improves students’ critical thinking skills, including the ability to analyze problems, evaluate options, and make logical decisions. Additionally, such learning strengthens communication, collaboration, and social interaction among students. It is recommended to provide teacher training, develop systematic learning models, and integrate entrepreneurship education into the curriculum, with further development incorporating digital technology and innovative learning models. This is expected to provide a clear roadmap for educators, curriculum designers, and policymakers in optimizing the implementation of entrepreneurship education as an effective tool to cultivate a generation that is both critical and innovative.